Assessment of quality of obstetric care in Zimbabwe using the standard primipara - Bothwell Takaingofa Guzha; Thulani Lesley Magwali; Bismark Mateveke; Maxwell Chirehwa; George Nyandoro; Stephen Peter Munjanja (BMC, 2018)
Abstract Background To improve maternity services in any country, there is need to monitor the quality of obstetric care. There is usually disparity of obstetric care and outcomes in most countries among women giving birth in different obstetric units. However, comparing the quality of obstetric care is difficult because of heterogeneous population characteristics and the difference in prevalence of complications. The concept of the standard primipara was introduced as a tool to control for these various confounding factors. This concept was used to compare the quality of obstetric care among districts in different geographical locations in Zimbabwe. Methods This was a substudy of the Zimbabwe Maternal and Perinatal Mortality Study. In the main study, cluster sampling was done with the provinces as clusters and 11 districts were randomly selected with one from each of the nine provinces and two from the largest province. This database was used to identify the standard primipara defined as; a woman in her first pregnancy without any known complications who has spontaneous onset of labour at term. Obstetric process and outcome indicators of the standard primipara were then used to compare the quality of care between rural and urban, across rural and across urban districts of Zimbabwe. Results A total of 45,240 births were recruited in the main study and 10,947 women met the definition of standard primipara. The maternal mortality ratio (MMR) and the perinatal mortality rate (PNMR) for the standard primiparae were 92/100000 live births and 15.4/1000 total births respectively. Compared to urban districts, the PNMR was higher in the rural districts (11/1000 total births vs 19/ 1000 total births, p < 0.001). In the urban to urban and rural to rural districts comparison, there were significant differences in most of the process indicators, but not in the PNMR. Conclusions The study has shown that the standard primipara can be used as a tool to measure and compare the quality of obstetric care in districts in different geographical areas. There is need to explore further how the quality of obstetric care can be improved in rural districts of Zimbabwe.